2018
DOI: 10.1007/s11095-018-2368-7
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Stabilization and Disaggregation of Bevacizumab, Ranibizumab and Aflibercept in Dilute Solutions

Abstract: PurposeStudies were conducted to investigate dilute solutions of the monoclonal antibody (mAb) bevacizumab, mAb fragment ranibizumab and fusion protein aflibercept, develop common procedures for formulation of low concentration mAbs and identify a stabilizing formulation for anti-VEGF mAbs for use in in vitro permeation studies.MethodsExcipient substitutions were screened. The most stabilizing formulation was chosen. Standard dilutions of bevacizumab, ranibizumab and aflibercept were prepared in PBS, manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Additionally, protein aggregation can occur during or after the administration of protein in a therapeutic context. 56,57 Multiple disorders and ailments such as myocardial infarction, diabetes, and cancer can be cured using commercially available protein-based products. At present, hundreds of such products are in the preclinical and clinical development stages.…”
Section: Consequences Of Protein Aggregationmentioning
confidence: 99%
“…Additionally, protein aggregation can occur during or after the administration of protein in a therapeutic context. 56,57 Multiple disorders and ailments such as myocardial infarction, diabetes, and cancer can be cured using commercially available protein-based products. At present, hundreds of such products are in the preclinical and clinical development stages.…”
Section: Consequences Of Protein Aggregationmentioning
confidence: 99%
“…Their SE-HLPC method uses a new marketed column designed for antibodies with a lower limit of detection (LOD) of 2.19 ng/mL and a lower limit of quantification (LLQ) of 8.79 ng/mL for bevacizumab and ranibizumab. Aflibercept LOD and LLQ were 8.79 and 17.578 ng/mL, respectively [85]. No in vivo studies were found that used HPLC as an analytical method for anti-VEGF drugs.…”
Section: Pharmacokinetic Considerationsmentioning
confidence: 99%
“…Thus, the aggregates that were present in the bulk solutions of PPI10 and PPI13 were reversible and dissociated slowly upon dialysis, dilution, and storage of the antibodies in the histidine buffer used in this work. Aggregate dissociation upon buffer exchange and dilution was previously reported but is outside the scope of our work …”
Section: Resultsmentioning
confidence: 76%
“…Aggregate dissociation upon buffer exchange and dilution was previously reported but is outside the scope of our work. 36 3.4. Comparison between ReFOLD, MSF, and Aggregation during Storage.…”
Section: Resultsmentioning
confidence: 99%